PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN DI PUSKESMAS TEMPEL I SLEMAN - Pramudyo, Anung; Faiturohmi, Fika (PRIMA EKONOMIKA, 2020)
Research aims to understand influence in partial and simultaneous to the quality of service and facilities to satisfaction patients at Puskesmas Tempel I Sleman. The research is quantitative research. The sample techniques used in this research was purposive sampling. This research using samples from 100 patients. The method of analysis data using multiple linear regression and the hypothesis done by t test and the F test. The result showed that quality of services (X1) and facilities (X2) whether partial and simultaneous influences satisfaction patients (Y) at Puskesmas Tempel I Sleman. The test determination shows that 92 % satisfaction patients affected by the quality of services and facilities, the remaining of 8 % influenced by variables others described in this study. Key Words: Quality, Service, Satisfaction, facilities